Microbiological, clinical and molecular findings of non-typhoidal Salmonella bloodstream infections associated with malaria, Oriental Province, Democratic Republic of the Congo. Issue 1 (December 2016) - Falay, Dadi; Kuijpers, Laura; Phoba, Marie-France; De Boeck, Hilde; Lunguya, Octavie; Vakaniaki, Emmanuel; Bertrand, Sophie; Mattheus, Wesley; Ceyssens, Pieter-Jan; Vanhoof, Raymond; Devlieger, Hugo; Van Geet, Chris; et al.
Abstract Background In sub-Saharan Africa, non-typhoidalSalmonella (NTS) can cause bloodstream infections, referred to as invasive non-typhoidalSalmonella disease (iNTS disease); it can occur in outbreaks and is often preceded by malaria. Data from Central Africa is limited. Methods Clinical, microbiological and molecular findings of NTS recovered in a blood culture surveillance project (2009–2014) were analyzed. Results In March-July 2012 there was an epidemic increase in malaria infections in the Oriental Province of the Democratic Republic of the Congo (DRC). In one referral hospital, overall hospital admissions in June 2012 were 2.6 times higher as compared to the same period in the years before and after (336 versus an average of 128 respectively); numbers of malaria cases and blood transfusions were nearly three- and five-fold higher respectively (317 versus 112 and 250 versus 55). Case fatality rates (in-hospital deaths versus all admissions) peaked at 14.6 %.Salmonella Typhimurium andSalmonella Enteritidis together accounted for 88.9 % of pathogens isolated from blood cultures collected during an outreach visit to the affected districts in June 2012. Children infected withSalmonella Enteritidis (33 patient files available) tended to be co-infected withPlasmodium falciparum more often than children infected withSalmonella Typhimurium (40 patients files available) (81.8 % versus 62.5 %). Through the microbiological surveillance project (May 2009–May 2014) 113 unique NTS isolates were collected (28.5 % (113/396) of pathogens); most (95.3 %) were recovered from children < 15 years.Salmonella Typhimurium (n  = 54) andSalmonella Enteritidis (n  = 56) accounted for 47.8 % and of 49.6 % NTS isolates respectively. Multilocus variable-number tandem-repeat analysis (MLVA) revealed more heterogeneity forSalmonella Typhimurium than forSalmonella Enteritidis. Most (82/96, 85.4 %) NTS isolates that were available for antibiotic susceptibility testing were multidrug resistant. All isolates were susceptible to ceftriaxone and azithromycin. Conclusion During the peak of an epidemic increase in malaria in the DRC in 2012, a high proportion of multidrug resistantSalmonella Typhimurium andSalmonella Enteritidis were isolated from blood cultures. Overall, the two serovars showed subtle differences in clinical presentation and genetic diversity.